Community Partnership Program to Increase Competitiveness of Batik Tulis in Kampoeng Jetis Sidoarjo - Tjahjani IK; Hatta M; Wahyudi A (Kontribusia : Research Dissemination for Community Development, 2018)
In this Community Partnership Program activity, we have 2 Partners, namely Batik Tulis artisans in the smallindustrial Kampoeng Batik Jetis Village Sidoklumpuk Jetis urban Village Head Lemah Putro, Sub District Sidoarjo District Sidoarjo. They are the owner of SME Batik Amri Jaya and owner of SME Batik Namiroh, which turned out to have the same problems, such as 1). Field Production, related to the use of some equipment in the current batik process that is not ergonomic, and 2). Field of Management; a. Daily production administration management, b. The absence of a product catalogue typical Kampoeng Batik Jetis c. Sales of conventional products, d. Not optimal supervision of production. In the field of production, the solution offered is the innovation of some equipment in the process of batik by applying the concept of ergonomics; a. the desk of the pattern for imitating the model, b. Chair of a batik maker, c. Modified LPG stove and candle filter. While in the field of management, conduct training and assistance with the material a) The importance of comfort and health in work (the concept of ergonomics), b). Production of daily production reports, c). Manufacture of product design and catalogue, d). E-commerce Marketing, and e). Optimization of production supervision function, business management, and production efficiency. Community Partnership Program activities are implemented so that all parties benefit as expected, among others: increased knowledge and insight of batik maker, sales turn over, the realization of effective and efficient management, which ultimately can increase the productivity, competitiveness, and independence of partners so as tocontribute to the welfare of people in the area.